miR-338-3p targets RAB23 and suppresses tumorigenicity of prostate cancer cells - Wang, Yuxiong (Am J Cancer Res, 2018)
MicroRNA-338-3p (miR-338-3p) has been implicated in several cancers; however, its role in human prostate cancer remains unknown. In this study, we observed downregulation of miR-338-3p in prostate cancer tissues and cell lines. Forced expression of miR-338-3p suppressed prostate cancer cell proliferation, migration, and invasion in vitro and tumor growth in vivo, while apoptosis was induced. Further experiments revealed that RAB23 is a target of miR-338-3p because miR-338-3p bound directly to the 3’-untranslated region (3’-UTR) of RAB23 mRNA, thereby reducing both the mRNA and protein levels of RAB23. Reintroduction of RAB23 attenuated the inhibitory effects of miR-338-3p on proliferation, migration, and invasiveness of prostate cancer cells. In clinical samples, miR-338-3p levels negatively correlated with RAB23 expression, which was upregulated in prostate cancer. Collectively, these results indicate that miR-338-3p acts as a tumor suppressor in prostate cancer by directly targeting RAB23.